PERAN KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN PT. KEIHIN INDONESIA - Nia Robiah Monika; Trisnawati Kusumawardhani (Interpretasi: Communication & Public Relations, 2022)
Organizational communication is the sending and receiving of various organizational messages by formal and informal groups within an organization. The existence of good organizational communication determines good corporate performance. The purpose of this study was to identify the role of corporate communication in improving employee morale at PT KEIHIN INDONESIA (KHI). Data collection was done through direct field observations, in-depth interviews, and documentation. The research was conducted using a qualitative approach with a constructivist paradigm. The theory used is organizational communication theory. From this research, it can be concluded that:(1) Point KHI is a company that pays attention to open communication with all parties involved in order to avoid miscommunication and misunderstanding. (2) Communication patterns at KHI adhere to the organizational communication pattern of downward communication, upward communication, and horizontal communication. (3) There is centralization of decision-making/policy-making when the interests of the entire company are at stake rather than the interests of just one or more departments.